(untitled) (Iraqi Journal of Medical Sciences, 2023)
Polycystic ovary syndrome (PCOS) is one of the most common healthy problems that frequently affects women during her reproductive life. It is a prevalent endocrinopathy that affects 6-10% of women in reproductive age. The pathophysiology of the condition is complex it caused by a hormonal imbalance and it is considered as a complex illness resulting from the combinations of intrauterine, hereditary, hormonal, and environmental variables. PCOS increases the chance of women to have type 2 diabetes, dyslipidemia, and systemic arterial hypertension. They also have a higher accidental of having a heart disease during menopause. Keywords: Polycystic ovary syndrome (PCOS), pathogenesis, clinical manifestations Citation: Farhood RG, Alshimerry AF. The role of hormonal and genetic factors in the pathogenesis of polycystic ovary syndrome: A review. Iraqi JMS. 2023; 21(2): 260-268. doi: 10.22578/IJMS.21.2.14